Risk Management Strategies in Salesforce Project Delivery: A Case Study Approach - Umababu Chinta; Shalu Jain; Anshika Aggarwal (Innovative Research Thoughts, 2021)
In the dynamic realm of Salesforce project delivery, effective risk management is crucial to ensure successful outcomes and mitigate potential issues that could impact project timelines, budgets, and overall quality. This research paper explores risk management strategies specifically within the context of Salesforce implementations, employing a case study approach to provide a nuanced understanding of how risks are identified, assessed, and mitigated in real-world scenarios. The study begins with a comprehensive review of the theoretical foundations of risk management in project management, emphasizing its importance in Salesforce projects due to the platform's complexity and the custom nature of many implementations. It highlights common risk categories, including technical challenges, resource constraints, and stakeholder engagement issues. To provide practical insights, the paper examines three detailed case studies of Salesforce projects undertaken by different organizations. Each case study offers a unique perspective on the risk management strategies employed, from initial risk identification and assessment through to the implementation of mitigation measures and the evaluation of their effectiveness. The cases cover a range of project sizes and industries, providing a broad view of the challenges faced and the solutions implemented.